The German adaptation of the Cambridge pulmonary hypertension outcome review (CAMPHOR) - Cima, Katharina; Grünig, Ekkehard; Benjamin, Nicola (Health and quality of life outcomes, 2012)
Individuals with precapillary pulmonary hypertension (PH) experience severely impaired quality of life. A disease-specific outcome measure for PH, the Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) was developed and validated in the UK and subsequently adapted for use in additional countries. The aim of this study was to translate and assess the reliability and validity of the CAMPHOR for German-speaking populations.